Diguanylate cyclase Dgc1 synthesizes c-di-GMP and modulates WL gum exopolysaccharide production in Sphingomonas sp. WG - Hui Li; Yanhui Jia; Hangxu Liu; Zaimei Zhang; Mengqi Chen; Huiyu Zheng; Mengqing Xu; Mengmeng Zang; Dong Wang; Yawei Sun; Hu Zhu; Jiqian Wang (Bioresource Technology, 2026)

Low-intensity electrical stimulation enhances phthalate ester biodegradation by activated sludge through real-time multi-scale regulation - Huabo Gong; Zhuo-Ning Xian; Jinwen Hu; Jinming Luo; Yawei Wang; Xiaowei Liu; Nanwen Zhu (Water Research, 2026)

Nitrogen-doped pyrite composite for enhanced Fe(III)/Fe(II) cycling and broad-spectrum pollutant degradation via peroxymonosulfate activation - Yan Yan; Zhenjie Li; Chunwei Liu; Yuan Qiao; Caiping Hu; Longquan Zhang; Xiaoguo Shi; Yizhe Zhao; Yawei Gu; Wenyu Wang (Process Safety and Environmental Protection, 2026)

Nitrogen sources and concentrations shape algal odor compounds: Key drivers of β-cyclocitral and β-ionone in water bodies of the lower Yangtze River - Sicheng Yin; Youyin Hu; Yawei Xing; Xianyun Wang; Erik Jeppesen; Liqing Wang; Wei Zhang (Journal of Environmental Sciences, 2026)

Decoding flood hazard responses to reticular river network changes using interpretable machine learning - Shanheng Huang; Peng Wang; Zulin Hua; Yueyang Dong; Rongxu Chen; Yawei Hu; Shimin Tian (Journal of Hydrology, 2026)

Integrated Heart Rate Monitoring and Transcriptomic Analyses Reveal Distinct Responses to Hypo- and Hypersalinity Stress in Abalone - Nan Chen; Run Hu; Yun Chen; Weiwei You; Caihuan Ke; Yawei Shen (Fishes, 2026)
In the context of global climate change, intensified salinity fluctuations driven by altered precipitation, extreme rainfall events, and typhoons have emerged as a major threat to coastal mollusk aquaculture. In this study, integrated physiological and transcriptomic analyses were performed to investigate the responses of Pacific abalone (DD, Haliotis discus hannai) and its hybrid (DF, H. discus hannai ♀ × H. fulgens ♂) to hypo- and hypersalinity stress. Two salinity breakpoints (BPS1 for hyposalinity, BPS2 for hypersalinity) were identified using heart rate monitoring to indicate the osmotic tolerance thresholds of the abalone. The BPS1 and BPS2 values did not differ significantly between the DD and DF groups. However, a subsequent 30-day culture trial confirmed that exposure to the salinity level corresponding to BPS1 significantly reduced growth and survival of both DD and DF groups. To explore the molecular mechanisms underlying these two salinity breakpoints in abalone, the transcriptomes of hemocytes and gill tissues were profiled under both stress conditions. Both hypo- and hypersalinity stress induced pronounced transcriptomic responses in abalone, accompanied by upregulated differentially expressed genes (DEGs) significantly enriched in pathways like TNF and NF-κB signaling, including genes like piap, diap2, birc7-a, birc2, and birc3. However, abalone exhibited more intense responses to hypersalinity stress, as reflected by a greater number of annotated differentially expressed genes (DEGs) and more complex transcriptional regulation. Overall, this study integrates physiological assessment based on heart rate monitoring, aquaculture trials, and transcriptomic analysis to advance our mechanistic understanding of osmotic stress adaptation in abalone, while laying a scientific foundation for the sustainable development of abalone aquaculture under global climate change.

Organic fractions in wastewater enabled simultaneous removal of NO3− and Cr(VI) under VUV185 irradiation - Yawei Xie; Shijie Wu; Xunfang Hu; Jinliang Wang; Dehua Ma; Wei Zheng; Rui Liu; Hongyuan Liu (Journal of Environmental Management, 2026)

Cathodic periodate activation driven by photocatalytic fuel cell for ciprofloxacin degradation - Yawei Xie; Shijie Wu; Yaozu Jin; Xunfang Hu; Jinliang Wang; Miaomiao Ye; Dehua Ma; Wei Zheng; Rui Liu; Hongyuan Liu (Journal of Water Process Engineering, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Co-liquefaction of triacetyl cellulose (TAC) from waste LCDs and high-sulfur low-rank coal (HSLC) by sub/supercritical water: Synergistic effect, desulfuration, and resource recovery - Fu-Rong Xiu; Yawei Ju; Yan Zhang; Jiaqing Hu; Yingying Qi (Waste Management, 2026)

Impact of salinity on nitrogen cycling and microbial community functional potential in groundwater of the Yellow river delta - Huan Wang; Chuanshun Zhi; Yufei Jiao; Dan Xu; Wenfeng Gao; Yawei Kou; Xiancang Wu; Jing Bai; Hui Mu; Houliang Lu; Xiaonong Hu (Applied Geochemistry, 2026)

Corrigendum to “Self-regulated mineralization of CO2 capture products from functionalized ionic liquid into disc-shaped vaterite” [Chem. Eng. J. 522 (2025) 167956] - Yang Chen; Jingyi He; Yawei Zeng; Shaoyun He; Zhen He; Hui Hu (Chemical Engineering Journal, 2025)

Unraveling the health contributions of five key bioactives in virgin olive oil: A dose-based comparative review - Yunfei Huang; Wenqing He; Mengyao Zhao; David Julian McClements; Yawei Xu; Lu Li; Wanyi Dong; Xueqin Hu; Chunmei Li (Trends in Food Science & Technology, 2025)

Preparation of magnesia directly from brine Mg(OH)2 and its performance optimization: The role of ZrSiO4 additive - Chengqing Hu; Yibiao Xu; Yawei Li; Wen Yan (Journal of Environmental Chemical Engineering, 2025)

Self-regulated mineralization of CO2 capture products from functionalized ionic liquid into disc-shaped vaterite - Yang Chen; Jingyi He; Yawei Zeng; Shaoyun He; Zhen He; Hui Hu (Chemical Engineering Journal, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Mediating role of whole epigenome DNA methylation signatures in the association between copper and SGA - Weiwei Wu; Mengru Wang; Shan Li; Bole Zhang; Weixuan Hu; Yulin Li; Yongliang Feng; Yawei Zhang; Suping Wang (Journal of Trace Elements in Medicine and Biology, 2025)

Water erosion control through vegetation restoration: Mechanisms and contributions of vegetation components in Robinia Pseudoacacia forests - Yang Li; Yawei Hu; Jiongchang Zhao; Jianjun Zhang (CATENA, 2025)

Sufficient burial depth is a prerequisite for Chinese cyclina (Cyclina sinensis) to maintain normal life activities - Yurou Ma; Shiyu Yan; Zhengyu Shao; Guolong Zhou; Ang Hu; Yawei Bu; Huimin Wang; Xinqi Lv; Jianyu Liu; Yihua Chen; Zhiguo Dong (Aquaculture, 2025)

Measurement and modeling of canopy interception loss of evergreen, deciduous and mixed forests in a subhumid watershed on the Loess Plateau, China - Jiongchang Zhao; Yang Yu; Yawei Hu; Matthias Beyer; Jianjun Zhang (Journal of Hydrology, 2025)

Distribution, removal and potential factors affecting antibiotics occurrence in leachate from municipal solid waste incineration plants in China - Xuan Rui; Huabo Gong; Jinwen Hu; Haiping Yuan; Yawei Wang; Lixia Yang; Nanwen Zhu (Water Research, 2025)

The Combined Effect Between SEPS1 Genetic Polymorphisms and Exposure to Metals on the Risk of Gestational Diabetes Mellitus - Weiwei Wu; Yulin Li; Weixuan Hu; Jing Zhao; Bole Zhang; Yongliang Feng; Yawei Zhang; Suping Wang (Biological Trace Element Research, 2025)

Polysaccharide-gated metal–organic framework nanoparticles for pH-triggered site-specific delivery and enhanced fungicide bioavailability - Chunlin Yang; Yawei Tang; Xiang Yao; Peijie Hu; Zaiyu Lu; Jinjing Xiao; Lihong Zhang; Haiqun Cao (Chemical Engineering Journal, 2025)

Hydrological interactions between surface water and groundwater in ancient manmade village tank cascade systems (VTCSs) in the dry zone of Sri Lanka - Suresh Indika; Dazhou Hu; Yuansong Wei; Isuru Yapabandara; Samadhi Athauda; Ashen Randika; Sangeeth Prasad; Titus Cooray; Madhubhashini Makehelwala; Hui Zhong; Yawei Wang; K.B.S.N. Jinadasa; et al. (Science of The Total Environment, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Interfacial evaporation and salt-blocking kinetics in Janus membrane for solar desalination - Haowei Hu; Jin Wang; Qi Zhao; Mengyuan Qiang; Qin Li; Lin Guo; Yawei Yang (Desalination, 2024)

Comprehensive characterization of the differences in metabolites, lipids, and volatile flavor compounds between Ningxiang and Berkshire pigs using multi-omics techniques - Qian Wang; Hu Gao; Yawei Fu; Yue Chen; Gang Song; Zhao Jin; Yuebo Zhang; Jie Yin; Yulong Yin; Kang Xu (Food Chemistry, 2024)

Drivers of change behind the spatial distribution and fate of typical trace organic pollutants in fresh waste leachate across China - Huabo Gong; Jinwen Hu; Xuan Rui; Yawei Wang; Nanwen Zhu (Water Research, 2024)

Effects of inorganic sodium on the soot generation of coal particle: Insights with PLIF and DFT calculation - Yawei Song; Sheng Su; Zheng Zhao; Jingyan Wang; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Song Hu; Jun Xiang (Fuel, 2024)

Hollow engineering of Co/N-doped C@carbon aerogel with hierarchical structure boosting interfacial polarization for ultra-thin microwave absorption and thermal insulation - Panpan Zhou; Shiyu Zhang; Wei Zhou; Chencheng Sun; Chengyao Hu; Shilin Yuan; Jiarui Li; Chang Liu; Yuchen Zhao; Yawei Kuang; Shuchang Wang; Qitu Zhang; et al. (Chemical Engineering Journal, 2024)

Exogenous iron caused osteocyte apoptosis, increased RANKL production, and stimulated bone resorption through oxidative stress in a murine model - Zengfeng Guo; Jiawen Wu; Yawei Hu; Jianhua Zhou; Qingmei Li; Yandong Zhang; Junde Zhang; Linbo Yang; Shenghang Wang; Hao Zhang; Jiancheng Yang (Chemico-Biological Interactions, 2024)

Linking the removal of enrofloxacin to the extracellular polymers of microalgae in water bodies: A case study focusing on the shifts in microbial communities - Youyin Hu; Shangsheng Sun; Xuewei Gu; Ziyi Li; Jialin Zhang; Yawei Xing; Liqing Wang; Wei Zhang (Environmental Science and Pollution Research, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Research on the direction perception of cruising copepods by the fish lateral line using pressure difference matrix and residual neural network regression method - Yawei Zhu; Yiyuan Gao; Zhaohang Ding; Changran Li; Hao Ding; Yonggang Guo; Dean Hu (Ocean Engineering, 2024)

Application of Hydraulic Sensitivity Indicators in Improving Canal Control Capabilities for Irrigation Systems - Yumiao Fan; Xiaohui Jin; Haorui Chen; Yawei Hu; Zhanyi Gao (Water Resources Management, 2024)

Supplementation with Akkermansia muciniphila improved glucose metabolism disorder in common carp (Cyprinus carpio L.) - Guokun Yang; Aixia Jiang; Huimin Cai; Fu You; Shengkui Wu; Yanmin Zhang; Xindang Zhang; Yawei Shen; Xulu Chang; Wenpan Hu; Keke Li; Xiaolin Meng (Aquaculture, 2023)

Analytical solution for the temperature field of an elliptical tunnel in cold regions - Yanhu Zhao; Jing Zhang; Linjing Li; Taotao Hu; Yawei Zhao (Cold Regions Science and Technology, 2023)

Getting insight into the oxidation of SO2 to SO3 over P modified VW/Ti catalyst: Effect and inhibition mechanism - Zijun Yin; Yuxiu Zhong; Jingwen Lu; Tao Liu; Yawei Song; Mengxia Qing; Lele Wang; Yi Wang; Song Hu; Sheng Su; Jun Xiang (Chemical Engineering Journal, 2023)

From bitter to delicious: properties and uses of microbial aminopeptidases - Yawei Wang; Puying Zhao; Ying Zhou; Xiaomin Hu; Hairong Xiong (World Journal of Microbiology and Biotechnology, 2023)

Multi-Tunnel Triboelectric Nanogenerator for Scavenging Mechanical Energy in Marine Floating Bodies - Ziyi Zhang; Zhiyuan Hu; Yan Wang; Yawei Wang; Qiqi Zhang; Dehua Liu; Hao Wang; Minyi Xu (Journal of Marine Science and Engineering, 2022)
The ocean has an abundant reserve of wave energy, which is considered to be a clean, widely distributed and inexhaustible resource. Triboelectric nanogenerators (TENGs) have been regarded as a reliable technology for harvesting wave energy due to its robustness and efficiency in scavenging random mechanical energy. In this study, a wave energy harvesting multi-tunnel TENG (MT-TENG) has been proposed, which could be integrated easily with ocean buoys. The MT-TENG consists of polytetrafluoroethylene (PTFE) balls and a multi-tunnel frame, which could convert wave energy into electrical energy. The multi-tunnel design also avoids possible mutual obstruction of the PFTE balls during the movement. Compared with the flat type structure, the multi-tunnel structure could enhance output performance obviously. With an agitation frequency of 2 Hz and vibration amplitude of 130 mm, the MT-TENG has a peak power density of 8.3 W/m3, which is five times that of the flat type structure TENG. By integrating with a life buoy and floating pipe line, the MT-TENG could harvest wave energy to light LEDs continuously, which could provide a new solution for maritime rescue and night offshore oil delivery warning.

Changing incidence and projections of thyroid cancer in mainland China, 1983–2032: evidence from Cancer Incidence in Five Continents - Mandi Li; Jiao Pei; Minghan Xu; Ting Shu; Chengjie Qin; Meijing Hu; Yawei Zhang; Min Jiang; Cairong Zhu (Cancer Causes & Control, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Antimicrobial Peptide JH-3 Effectively Kills Salmonella enterica Serovar Typhimurium Strain CVCC541 and Reduces Its Pathogenicity in Mice - Lei Wang; Xueqin Zhao; Xiaojing Xia; Chunling Zhu; Wanhai Qin; Yanzhao Xu; Bolin Hang; Yawei Sun; Shijun Chen; Huihui Zhang; Jinqing Jiang; Jianhe Hu; et al. (Probiotics and Antimicrobial Proteins, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Three-dimensional distributed DC/IP method for altered tectonite-type gold ore deposits exploration: a case study of the Jiaojia gold metallogenic belt, Eastern China - Jiayong Yan; Yawei Zhang; Kun Zhang; Yongqian Zhang; Hao Hu; Zhihui Wang (Acta Geophysica, 2018)

Variation of phytoplankton functional groups modulated by hydraulic controls in Hongze Lake, China - Chang Tian; Haiyan Pei; Wenrong Hu; Daping Hao; Martina A. Doblin; Ying Ren; Jielin Wei; Yawei Feng (Environmental Science and Pollution Research, 2015)

Uncertainty analysis of SPI calculation and drought assessment based on the application of Bootstrap - Yi‐Ming Hu; Zhong‐Min Liang; Yong‐Wei Liu; Jun Wang; Lei Yao; Yawei Ning (International Journal of Climatology, 2015)
The Standardized Precipitation Index ( SPI ) has been widely used to monitor the drought status. In the estimation of SPI , an appropriate probability distribution function ( APDF ) is required to fit precipitation series with different timescales, such as 3‐month, 9‐month and so on. Then the standard normal distribution function is used to transform the cumulative probability derived from APDF to calculate the SPI value. Obviously, the estimation accuracy of SPI particularly depends on the sample that influences the selection of PDF and parameter estimation. However, the size of the observed sample is usually small, and it cannot perfectly present the statistical property of the population, which usually causes the uncertainty on calculation of SPI and in turn results in the uncertainty of drought assessment. Due to the existence of gap between the estimated SPI and the true SPI , when one obtains the estimation of SPI , it is necessary to know the reliability or uncertainty of the estimated SPI . In this article, a new method based on the Bootstrap method was put forward to analyse the impact of sampling uncertainty on the estimation of SPI and drought assessment. Through repeating samples from the original sample, a large number of Bootstrap samples are constructed, and based on each Bootstrap sample, the corresponding estimation of SPI for the given event can be obtained. Therefore, the sampling distribution of SPI for the given event can also be derived, on which both the point estimation and interval estimation of SPI for the given precipitation event can be provided, and the overall assessment of a drought event could be achieved. The case study shows that, compared with the original SPI calculation method, the proposed method not only provides equivalent assessment results, but also has the capability to assess the impact of sampling uncertainty on the uncertainty of SPI calculation and drought assessment.

Spatiotemporal distribution pattern of cyanobacteria community and its relationship with the environmental factors in Hongze Lake, China - Ying Ren; Haiyan Pei; Wenrong Hu; Chang Tian; Daping Hao; Jielin Wei; Yawei Feng (Environmental Monitoring and Assessment, 2014)

Calcineurin Plays an Important Role in the Shell Formation of Pearl Oyster (Pinctada fucata) - Changzhong Li; Yilin Hu; Jian Liang; Yawei Kong; Jing Huang; Qiaoli Feng; Shuo Li; Guiyou Zhang; Liping Xie; Rongqing Zhang (Marine Biotechnology, 2010)